Factors Affecting the Development of Small Business and Private Entrepreneurship (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article highlights the ways to achieve effective economic growth through the development of small business and private entrepreneurship and the provision of employment for the population through the development of small business and private entrepreneurship, the wide attraction of foreign investment funds, as well as the state support of entrepreneurship. In addition, a scientific proposal and practical recommendations have been developed for the establishment of production activities with the rational use of available resources.